1995
DOI: 10.1116/1.587897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TMG/AsH3 ratio on GaAs molecular layer growth

Abstract: Growth of undoped ZnSe on (100) GaAs by molecular-beam epitaxy: An investigation of the effects of growth temperature and beam pressure ratio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…͑1͒ At the TEI injection pressures below 2.5ϫ10 Ϫ6 Torr, the growth rate decreases with the TEI injection pressure, and a specular surface is obtained. 30 Therefore, it is assumed that the droplets result from anomalous reactions at low TEI injection pressure, such as the enhancement of TEI decomposition, which results from its large diameter, and the increase in the mean free path of the indium atoms' migration, which results from their low density. Especially at the TEI injection pressure of 10 Ϫ6 Torr, an almost specular sur- FIG.…”
Section: B Injection Pressure Dependence Of Teimentioning
confidence: 99%
See 2 more Smart Citations
“…͑1͒ At the TEI injection pressures below 2.5ϫ10 Ϫ6 Torr, the growth rate decreases with the TEI injection pressure, and a specular surface is obtained. 30 Therefore, it is assumed that the droplets result from anomalous reactions at low TEI injection pressure, such as the enhancement of TEI decomposition, which results from its large diameter, and the increase in the mean free path of the indium atoms' migration, which results from their low density. Especially at the TEI injection pressure of 10 Ϫ6 Torr, an almost specular sur- FIG.…”
Section: B Injection Pressure Dependence Of Teimentioning
confidence: 99%
“…30 However, the growth rate of 1 ML/cycle cannot be achieved even if the injection time or the injection pressure of TBP is increased, as shown in Figs. It is expected that the growth rate increases with the TBP injection time or pressure because it has been reported that the growth rate approaches 1 ML/cycle with the increase in the injection time of AsH 3 in MLE growth of GaAs using TMG and AsH 3 as sources.…”
Section: G Approaches For 1 Ml/cycle and Low Gas Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 9 shows the growth rate per cycle at 513 "C versus AsH3 dosage, which means the product of the pressure and the duration of AsH3 in each cycle [16]. In the figure, there were three different characteristics of the growth rate versus AsH3 dosage.…”
Section: Liquid Phase Epitaxial Growth Of Gaas By the Temperature Difmentioning
confidence: 99%
“…The dependence of the growth rate per cycle on the evacuation duration of AsH3 and TMG was investigated (11) as shown in Fig. 11 [16]. On the monolayer growth condition, AsH3 was introduced for 100 s at the pressure of 1 X 10" Torr and TMG for 16 s at 5 X 10''…”
Section: Evacuation Of Asand and Tmgmentioning
confidence: 99%